Policies to regulate data sharing of cohorts via data infrastructures: An interview study with funding agencies. (December 2022) - Devriendt, Thijs; Shabani, Mahsa; Borry, Pascal
Highlights: Funding agencies do not generally endorse data sharing mandates for various reasons. Funding agencies lack monitoring mechanisms for cohort data sharing. Funding agencies are not imposing conditions on data access committees. Certification schemes to recommend platforms to researchers are lacking. Abstract: Background: Platforms are being constructed to stimulate cohort data sharing. Nevertheless, many policy barriers impede data sharing. Various interventions have been proposed to address these barriers, including incentive creation and data sharing mandates for researchers. Aim: To understand funding agencies' perspectives on policy interventions to encourage data sharing. Methods: Members of funding agencies were recruited to participate in semi-structured interviews. Nearly all funding agencies are situated in European countries. Interview transcripts were analyzed through inductive content analysis. Results: Mandates for cohort data sharing are not supported by agencies due to data protection regulations and the preconditions for issuing mandates. Recommendation of platforms may be based on certification schemes, such as repository accreditation. Monitoring mechanisms for cohort data sharing are currently absent, which complicates assessing compliance of researchers with funding agencies' policies and evidence production. Funding agencies are not imposing conditions on data access committees. Conclusions: Policy measures that, in some ways, restrict the decision-making authority of researchers in terms of data sharing are not generally supported. Concrete steps are proposed to enable evidence-based policy making. Incentive design is paramount if funding agencies do not wish to impose restrictions on the decision-making authority of researchers.